Commensal microorganisms ameliorate the adverse effects of high wheat starch diet on the growth performance, glucose and lipid metabolisms in juvenile largemouth bass, Micropterus salmoides - Bi-Yun Zhang; Hong-Ling Yang; Ze-Hui Yuan; Xiao-Ou Sun; Jia-Hao Yin; Jun-Ji Xu; Guo-He Cai; Yun-Zhang Sun (Aquaculture Reports)
Largemouth bass (Micropterus salmoides) is poor at utilizing starch, and it is not clear whether commensal microorganisms can alleviate the adverse influences of high wheat starch in M. salmoides. Here, twelve autochthonous microorganisms with amylase producing abilities were isolated from the M. salmoides fed with diets containing 6 %, 12 %, or 18 % starch. Among them, Citrobacter freundii F1, Bacillus altitudinis F7, Enterococcus casseliflavus D12, Plesiomonas shigelloides D15, Bacillus cabrialesii D16, Citrobacter portucalensis K25 and Serratia oryzae K28 showed no hemolytic activity and were safety for M. salmoides. A 42-d feeding experiment was performed to study the functions of the seven microorganisms. A total of 810 fish (5.9 ± 0.01 g) were equally distributed into 9 groups. The control groups C6 and C18 were respectively fed with 6 % and 18 % wheat starch diets, the groups F1, F7, D12, D15, D16, K25 and K28 were fed with 18 % wheat starch diets respectively supplemented with 1.0×108 CFU/g C. freundii F1, B. altitudinis F7, E. casseliflavus D12, P. shigelloides D15, B. cabrialesii D16, C. portucalensis K25 and S. oryzae K28. The results indicated that compared with 6 % starch, 18 % level inhibited the growth performance, increased the hepatic glycogen and fat contents, improved the activities of glycolysis-related enzymes (hexokinase (HK), glucokinase (GK), phosphofructokinase (PFK), pyruvate kinase (PK)), decreased the activities of gluconeogenesis-related enzymes, pyruvate carboxylase (PC) and phosphoenolpyruvate carboxykinase (PEPCK), promoted the activity of lipid synthases-related enzyme carnitine palmitoyl transferaseⅠ (CPT1) and reduced the activity of lipolytic enzymes-related lipoprotein lipase (LPL). C. freundii F1, P. shigelloides D15, C. portucalensis K25 and S. oryzae K28 had relatively poor alleviating effects, while B. altitudinis F7, E. casseliflavus D12 and B. cabrialesii D16 significantly promoted the final body weight (FBW), weight gain rate (WGR), specific growth rate (SGR), protein efficiency ratio (PER), decreased feed conversion rate (FCR), significantly reduced the hepatic glycogen and fat contents, decreased the activities of glycolysis-related enzymes (HK, GK, PK), improved the activities of gluconeogenesis-related enzymes (PC, PEPCK), reduced the activity of lipid synthases-related enzyme CPT1 (P < 0.05), which proved that these three strains could effectively alleviate the negative effects of high starch in M. salmoides. In conclusion, among the seven autochthonous microorganisms, B. altitudinis F7, E. casseliflavus D12 and B. cabrialesii D16 presented better potential advantages in improving glucose and lipid metabolisms, thus promoting the growth performance of M. salmoides fed with high wheat starch diet.